Biomechanical Effects of Δ9-Tetrahydrocannabinol (THC) and Cannabidiol (CBD), the Major Constituents of Cannabis, on Tendon to Tendon Healing in a Sprague Dawley Rat Achilles Tendon Surgical Repair Model. Issue 7 (31st July 2020) - Stauch, Chris; Ammerman, Brittany; Aynardi, Michael; Garner, Matthew; Lewis, Greg; Morgan, Daniel; Dhawan, Aman
Objectives: Use of Cannabis is common amongst athletes and the U.S. population at large. Use of Cannabinoid Oil is being increasingly utilized for a number of different pathologies, injuries, and ailments due to anecdotal evidence of its efficacy. Due to the current United States Opioid crisis, Δ9-Tetrahydrocannabinol (THC) and Cannabidiol (CBD), the two major constituents of cannabis, are currently being evaluated as potential safer alternatives to narcotic pain medicines. The effects of recreational and/or therapeutic THC and CBD on musculoskeletal injury and healing however remain largely unknown. Our purpose was to evaluate the biomechanical effects of THC and CBD on tendon to tendon healing in a Sprague Dawley Achilles Tendon injury and surgical repair model. Methods: 33 Sprague Dawley rats were randomly assigned into control (1 ml/kg/day of vehicle containing 5% Cremaphor, 5% ethanol, and 0.9% saline n=12), THC (3 mg/kg/day n = 12), or CBD (3 mg/kg/day n=9) treatment groups. Surgical transection and repair of the Achilles tendon was performed and all rats began subcutaneous administration of their respective drug treatment the day of surgery and for 4 subsequent days, followed by sacrifice. Load to failure and stiffness were calculated from load displacement data during tensile load testing on a MTS machine. One-way ANOVA with heterogeneous variance was utilized for evaluation. Means and 95% confidence intervals were also determined. Results: The CBD group demonstrated the highest mean load to failure of 17.5 N (15.1-19.8 N), with the THC group having the second highest mean load to failure at 17.3 N (15.3-19.2 N), and the control group reporting the lowest at 15.2 N (12.1-18.3 N). No statistical difference was observed between CBD/control (p = 0.25), THC/control (p = 0.29), or CBD/THC groups (p = 0.92, Figure 1A). The THC group reported the highest mean stiffness of 3.9 N/mm (2.7-5.1 N/mm). The CBD and control groups demonstrated mean stiffness values of 3.5 N/mm (2.9-4.1 N/mm) and 3.5 N (2.7-4.3 N/mm), respectively. No statistically significant differences were observed between THC/control (p = 0.51), THC/CBD (p = 0.50), or CBD/control groups (p = 0.96) for stiffness (Figure 1B). Conclusion: Our investigation demonstrates that subcutaneous administration of CBD resulted in the highest mean load to failure while THC administration resulted in the highest mean stiffness of the three groups. This did not result however in a statistically significant difference between groups. In our small animal tendon-to-tendon repair model, use of THC or CBD did not result in decreased biomechanical characteristics, and there was a trend toward improved ultimate strength and stiffness as compared to control. Further evaluation with larger numbers of animals, and evaluating the potential synergistic effects of THC and CBD administered together are warranted. Figure 1.